Microbiological Profile of Neonatal Sepsis at a Maternity Hospital in Omdurman, Sudan - Manal Abdelaziz; Yassir Hamadalnil; Omaima Hashim; Tahane Bashir; E. S. Mahjoub (Sudan Journal of Medical Sciences)
Background: Neonatal sepsis is a clinical syndrome characterized by systemic signs of infection and accompanied by bacteremia in the first month of life. It is a major cause of morbidity and mortality in neonatal period. The study was conducted to determine microbiological profile and antibiogram of neonatal sepsis at Omdurman Maternity Hospital.